Panel Data Analysis in Identifying and Mapping Caused Factors of Financial Crises and Monetary Instability in Developing Countries - Tri Febrina Melinda; Yusuf Unggul Budiman; Iwan Henri Kusnadi; Lydia Gustina Putri; Dina Agnesia Sihombing (SEULANGA SYSTEM PUBLISHER, 2024)
This study aims to reveal the extent of macroeconomic instability, which has the characteristics of a financial crisis and inflation. To test the hypothesis, researchers use fixed effects and random effects estimators to assess the presence of individual and temporal effects. Macroeconomic fundamentals, especially the risk of devaluation and a drop in economic activity can be seen as early warning signs of banks becoming less solvent. They also play a big role in explaining how deposits changed during the crisis. Our findings highlight the unique features of the convertible monetary regime, reinforcing the belief that debtors will enjoy permanent protection against devaluation risks. This perception encourages the dollarization of bank portfolios, thereby increasing the financial system's solvency risks. There is also evidence that the regulatory framework in this area is weak when it comes to the financial system's exposure to devaluation risks and public debt risks. This is especially true when it comes to an institutional framework that makes it hard for government funding to be changed into other currencies. We find that inflation is a very persistent process during periods of high inflation. However, with the decline in inflation after the implementation of the convertibility regime, its persistence reduced significantly. The results show that non-rational persistence is currently not very high, suggesting that the costs of designing the economy should not be either. We find that univariate models tend to perform better over very short horizons. The results suggest that there may be advantages to using a combination of different models, provided they are informative about the relationship between inflation and its short- and long-run determinants.